Estimating Robot Induced Affective State using Hidden Markov Models - Kulic, D.; Croft, E. (ROMAN 2006 - The 15th IEEE International Symposium on Robot and Human Interactive Communication, 2006)
In order for humans and robots to interact in an effective and intuitive manner, robots must obtain information about the human affective state in response to the robot's actions. This secondary mode of interactive communication is hypothesized to permit a more natural collaboration, similar to the "body language" interaction between two cooperating humans. This paper describes the implementation and validation of a hidden Markov model for estimating human affective state in real-time, using robot motions as the stimulus. Inputs to the system are physiological signals such as heart rate, perspiration rate, and facial muscle contraction. Affective state was estimated using a two dimensional valence-arousal representation. A robot manipulator was used to generate motions simulating human-robot interaction, and human subjects were asked to report their response to the motions. The human physiological response was also measured. Robot motions were generated using both a nominal potential field planner and a recently reported safe motion planner that minimizes the potential collision forces along the path. The robot motions were tested with 36 subjects. This data was used to train and validate the HMM model. The results of the HMM affective estimation are also compared to a previously implemented fuzzy inference engine